United Kingdom : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Selected Issues paper of the United Kingdom analyzes the official projections of public pension spending and risks, as well as the strategy to increase private pension provision. It provides a comparison of stylized facts regarding business cycle developments in the three economies, and an analysis of how these cyclical differences reflect the way monetary policy changes impact the three economies. It analyzes the policy on Economic and Monetary Union membership; and also the interest rate changes in the United Kingdom and the United States compared with that in the euro area.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet